Characterizations of N(2, 2, 0) Algebras. (10th January 2016) - Deng, Fang-an; Chen, Lu; Tuo, ShouHeng; Ren, ShengZhang
Abstract : The so-called ideal and subalgebra and some additional concepts ofN ( 2, 2, 0 ) algebras are discussed. A partial order and congruence relations onN ( 2, 2, 0 ) algebras are also proposed, and some properties are investigated.